Analysis of Rice Farmers' Income in Kobisonta Village, East Seram Utara Seti District, Central Maluku Regency - Kasben, Nurhana; Sinay, Francisca Riconita; Louhenapessy, William George M (Universitas Pattimura, 2025)
This study aims to analyse the production potential of rice farmers and their income levels in Kobisonta Village. The research utilises primary data collected through observation and questionnaires. The data analysis technique employed is quantitative analysis with a descriptive approach. The results indicate that the total revenue of rice farmers amounts to Rp. 312,500,000, with total production costs reaching Rp. 112,464,201, resulting in a net income of Rp. 200,035,799. Further analysis reveals that the primary factors influencing farmers' income are revenue and production costs. To increase their income, farmers are encouraged to optimise production efficiency by reducing unnecessary expenses. Additionally, diversification of agricultural activities and the adoption of modern agricultural technology can enhance productivity and farmers' welfare. Therefore, support from the government and related institutions is essential in providing production facilities and technical assistance for farmers.